Avaliação de serviços do SIBI-São Carlos: Um estudo de caso com utilização do método LIBQUAL+ - Pinto, Euzébio Luiz (Universidade Federal de São Carlos, 2012)
ABSTRACT Between March and May 2012, a quality assessment was carried out in two public libraries and one school-community library of the São Carlos Library System (SIBI-SC), by surveying the perception of their readers about the service provided and infrastructural aspects, using the LIBQUAL+® tool and semi-open interview techniques – including a type of approach based on questions from the Benevox® software, used in the Quality Assessment Program of USP libraries (PAQ-USP). This research was motivated by the demand from SIBISC – verified by the author of this work – to carry out a careful evaluation of the services and infrastructure of its libraries and to gain a deeper understanding of the public's perception of their services, as well as to assess the performance of LIBQUAL+® in relation to an audience – that of Brazilian public libraries – that is much more diverse than that of university and public libraries in countries with a greater tradition of reading (such as the USA and European countries) that the applications of that instrument present in the scientific literature normally involve. This study was guided by the theoretical framework – existing in the field of Service Assessment in Information Units – which is based on the research that Parasuraman and his team have developed since 1985 – which focuses on service assessment from the perspective of readers’ perceptions – and the development, by this team, of the SERVQUAL assessment instrument, with the adaptation of this instrument, carried out by the Association of Research Libraries and Texas A&M University, resulting in the creation of LIBQUAL+® - an assessment method specifically designed for libraries. The analysis of the data generated highlighted the need for several improvements related to information control (including investments in electronic resources and renewal of collections) and library infrastructure; on the other hand, it showed a good public perception of the services provided by these libraries. One of the public libraries, Euclides da Cunha, stood out for its excellent service performance and for the praise for its infrastructure, considered to be of superior quality to that of the other libraries evaluated. However, the context of the fieldwork revealed limitations related to LIBQUAL+® - both in terms of the difficulties in applying it to the public and in the survey of specific aspects of libraries that the instrument was unable to cover, which were complemented by qualitative data generated by semi-open interviews. The use of such interviews, associated with the statistical analysis of the qualitative data generated - made possible through the indexing process - allowed the dimensions of library evaluation considered by LIBQUAL+® to be approached in a more comprehensive manner, opening up the possibility for the development and use of new techniques for evaluating services in information units.
Evaluation of SIBI-São Carlos services: A case study using the LIBQUAL+ method
Keywords: Bibliotecas - Satisfação do usuário Bibliotecas; Libraries - User satisfaction; Information services; Libraries - Evaluation Quality management; Biblioteca pública; Avaliação de serviços; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::BIBLIOTECONOMIA::PROCESSOS DE DISSEMINACAO DA INFORMACAO